Analytical model for the combined effects of rotation and collisionality on neoclassical impurity transport. (14th February 2023) - Fajardo, D; Angioni, C; Casson, F J; Field, A R; Maget, P; Manas, P; ,; ,
Abstract: The influence of rotation, collisionality and trapped particle fraction on the magnitude and direction of neoclassical impurity transport in tokamaks is analyzed using an extensive database of drift-kinetic simulations with the NEO code. It is shown that an operational window opens at sufficiently high Mach number and low collisionality, where the magnitude of the temperature screening of impurities increases with higher rotation. If the collisionality increases, this effect is quickly lost and the temperature gradient then drives an inward impurity flux when rotation is present. The boundary between these two regimes is calculated as a function of the trapped particle fraction, and it is shown that plasma parameters achieved in recent JET experiments allow them to access the new beneficial regime, in accordance with observations of reduced tungsten accumulation. Applications to ASDEX Upgrade experiments where these effects become relevant are also presented, and the implications for ITER are discussed. A method for extracting the physically distinct Pfirsch–Schlüter (PS) and banana-plateau (BP) neoclassical flux components from the NEO output is introduced and employed to construct a model that describes them analytically at arbitrary rotation and collisionality. The beneficial behavior of the screening with rotation is found to be a BP effect, in contrast to the known detrimental role of rotation in the PS component. The new analytical model is able to reproduce the results of NEO when modeling radial profiles of transport coefficients from experimental kinetic profiles, with the added feature of isolating the BP and PS components for additional physical analysis, while remaining well suited for fast applications.